Silva, Al (audio interview #1 of 1) - Silva, Al; Briegel, Kaye, interviewer
INTERVIEW DESCRIPTION - Al Silva was interviewed in an office in the Signal Hill City Yard. TOPICS - family background; education; military; US Navy; municipal employment; housing and oil wells;Japanese school; gasoline service stations; oil industry; municipal employment; and Signal Hill Water Department;Signal Hill Water Department; education; municipal employment; Long Beach Gas Department; and Long Beach Airport; 6/28/1991